Genes Encoding Recognition of the Cladosporium fulvum Effector Protein Ecp5 Are Encoded at Several Loci in the Tomato Genome. Issue 5 (1st May 2020) - Iakovidis, Michail; Soumpourou, Eleni; Anderson, Elisabeth; Etherington, Graham; Yourstone, Scott; Thomas, Colwyn
Abstract: The molecular interactions between tomato and Cladosporium fulvum have been an important model for molecular plant pathology. Complex genetic loci on tomato chromosomes 1 and 6 harbor genes for resistance to Cladosporium fulvum, encoding receptor like-proteins that perceive distinct Cladosporium fulvum effectors and trigger plant defenses. Here, we report classical mapping strategies for loci in tomato accessions that respond to Cladosporium fulvum effector Ecp5, which is very sequence-monomorphic. We screened 139 wild tomato accessions for an Ecp5-induced hypersensitive response, and in five accessions, the Ecp5-induced hypersensitive response segregated as a monogenic trait, mapping to distinct loci in the tomato genome. We identified at least three loci on chromosomes 1, 7 and 12 that harbor distinct Cf-Ecp5 genes in four different accessions. Our mapping showed that the Cf-Ecp5 in Solanum pimpinellifolium G1.1161 is located at the Milky Way locus. The Cf-Ecp5 in Solanum pimpinellifolium LA0722 was mapped to the bottom arm of chromosome 7, while the Cf-Ecp5 genes in Solanum lycopersicum Ontario 7522 and Solanum pimpinellifolium LA2852 were mapped to the same locus on the top arm of chromosome 12. Bi-parental crosses between accessions carrying distinct Cf-Ecp5 genes revealed putative genetically unlinked suppressors of the Ecp5-induced hypersensitive response. Our mapping also showed that Cf-11 is located on chromosome 11, close to the Cf-3 locus. The Ecp5-induced hypersensitive response is widely distributed within tomato species and is variable in strength. This novel example of convergent evolution could be used for choosing different functional Cf-Ecp5 genes according to individual plant breeding needs.